RANCANG BANGUN PROTOTIPE SISTEM HEADING AUTOPILOT BERBASIS RATE-GYROSCOPE DAN MICROCONTROLLER - Widada, Wahyu (Indonesian Journal of Aerospace, 2006)
This paper discusses an experiment result of the prototype system feedback control for vehicle heading autopilot. The heading angle is measured with a rate-gyroscope and controlling with a control system based on a microcontroller and a stepper motor. This system is successfully realized within 0.5 degree of the error for heading angle. The accuracy of heading sensor is decrease due to vibration from stepper motor. To overcome such problem we recommended to use an analog lowpass filter and a mounting anti vibration.